The Effect of Job Mutation and Job Promotion on Job Satisfaction and Self-Efficacy, and its Implication on Job performance - Utomo, Hastho Joko Nur; Pujiastuti, Eny Endah; Sugiarto, Meilan; Ramadani, Noven (Jurnal Internasional Penelitian Bisnis Terapan, 2025)
This study examines the impact of job mutation and promotion on job satisfaction and self-efficacy at PT Bank Rakyat Indonesia Tbk Yogyakarta Regional Office. Using a quantitative approach with Partial Least Square (PLS) and SmartPLS 4.0, data were gathered from 150 employees who had experienced job transfers or promotions. The findings reveal that job transfers significantly enhance both job satisfaction and self-efficacy, whereas job promotions improve job satisfaction but do not affect self-efficacy. Job satisfaction positively influences self-efficacy and employee performance, but self-efficacy does not significantly impact performance. The study highlights that effective mutation and promotion strategies can boost job satisfaction and self-efficacy, thereby positively influencing employee performance. This research is notable for its focus on the Indonesian banking sector and its exploration of self-efficacy within the financial industry, addressing gaps or offering new insights in the literature. Managerial implications suggest that mutation and promotion policies should be customized to individual employee readiness to optimize job satisfaction and performance.